Sustainability Maturity Maturity Level of Indonesian College of Economics in Facing the Era of Change - Supriyatin (Best Journal of Administration and Management, 2023)
The purpose of this study is to determine the role that private tertiary institutions play in the process of achieving sustainability. Private tertiary institutions will need to be able to form relationships with a variety of parties, such as the private sector and the government sector, and formulate sustainability maturity levels in order to determine the extent to which tertiary institutions have reached a certain level of maturity. In this study, a descriptive research method is combined with a quantitative research methodology. According to research, several components of STIE Indonesia, such as Innovation and technology, Collaboration, Process, Purchase, motivation and incentives, health and safety, human resource development, and ethical behavior and human rights, are at the stage where they are gratifying or satisfying. Extraordinary or of a sophisticated nature. On the most fundamental or fundamental level, which involves knowledge management, the absence of conflicting interests, effective governance, and an absence of corruption. However, private universities have a responsibility to place a greater emphasis on sustainability reports, resources set aside for recycling, concerns regarding biodiversity and environmental issues, emission pollution into the air, water, and soil, and the existence of universities that start at the Beginning level.